Green Revolution’s Role and Impact: Organic Farming Potential for Indonesian Sustainable Agriculture - nFN Ashari; Juwaidah Sharifuddin; Zainal Abidin Mohammed; Nurul Nadia Ramli; Yong Farmata (Forum penelitian Agro Ekonomi, 2019)
In 1960s, Indonesia experienced serious rice insufficiency and was one of the largest rice importing countries. The government was encouraged to achieve rice self-sufficiency, i.e. implementing the green revolution (GR) technology through promoting modern agricultural inputs adoption. GR had helped Indonesia to achieve rice self- sufficiency in 1984. However, such technology deals with some problems, e.g. environmental destruction and farmers’ dependence on agrochemical industry.  Many consider organic farming system is the solution to address this issue as its practice offers the best way toward sustainable food production and resources use. Demand for organic rice is expected to increase in the future along with the population and income growth. However, prospect of organic rice farming is still uncertain as its adoption is very low. The main challenge is farmers’ unease on yield reduction. Other crucial problems are lack of technical know-how and government supports as well as increase in costs of land conversion and chemical contaminations from conventional farming. It is necessary to conduct more in-depth studies on the factors influencing farmers’ willingness to adopt organic farming. It will be useful for the government to design appropriate strategies and policies to accelerate organic rice farming adoption. AbstrakPada 1960-an, Indonesia mengalami kekurangan beras dan termasuk salah satu pengimpor beras terbesar di dunia. Pemerintah saat itu memprioritaskan pemenuhan beras dengan target swasembada dengan berbagai upaya, seperti penerapan teknologi revolusi hijau (RH) melalui penggunaan input pertanian modern. RH terbukti membuat Indonesia mencapai swasembada beras pada tahun 1984. Namun, teknologi tersebut juga telah menyebabkan dampak negatif, terutama kerusakan lingkungan dan petani sangat bergantung pada industri agro- kimia. Beberapa kalangan menganggap sistem pertanian organik adalah solusi untuk mengatasi masalah ini. Pertanian organik menawarkan cara terbaik untuk produksi pangan dan penggunaan sumber daya secara berkelanjutan dan ramah lingkungan. Permintaan beras organik diperkirakan akan meningkat di masa mendatang seiring dengan pertumbuhan penduduk dan pendapatan. Adopsi pertanian organik masih sangat lambat. Tantangan utama pertanian padi organik adalah kekhawatiran anjloknya hasil panen ketika melakukan konversi. Permasalahan  lainnya  adalah  kurangnya  pengetahuan  teknis  dan  dukungan  pemerintah,  mahalnya  biaya konversi dan kontaminasi bahan kimia dari pertanian konvensional. Diperlukan penelitian yang lebih mendalam tentang faktor-faktor yang memengaruhi petani untuk mengadopsi pertanian organik. Dengan demikian pemerintah dapat merancang strategi dan kebijakan yang tepat untuk mempercepat adopsi pertanian padi organik.